Deformasi Bendungan Cirata berdasarkan Analisis Data Instrumen Patok Geser - Dian Arief Pramudya Pratomo; Suharyanto; Pranoto Samto Atmojo (Universitas Negeri Gorontalo, 2021)
Concrete-faced rockfill dam (CFRD) has a similar weakness to other types of dams, namely deformation. Surface movement monuments can be used to monitor the deformation that occurs on the surface of the dam. Analysis of the monument's measurement data can show settlement and displacement trends that are closely related to the deformation of the dam itself. In this research, the monuments measurement data are compared to acceptance criteria from ICOLD, Sowers, Clements, Fell, and the Ministry of Public Works and Housing as outlined in the Guidelines for The Design and Construction of Concrete Membrane Stone Backfill Dams. This study aims to analyze data from surface movement monuments to determine the settlement and displacement of the dam based on the criteria of deformation. According to the obtained result, the first segment of surface monuments settlement values ranged from 0.028 to 0.165%, which meet the majority of the criteria. In addition, displacement values at the first segment of surface movement monuments were within 0.022 – 0.071%, which meets the ICOLD and Clements criteria. Meanwhile, for the second to fourth segments of surface movement monuments, settlement values of 0.007 – 0.102% were obtained, which still conform to the ICOLD and Fell criteria.